Analisa Potensi Longsor Dengan Metode SMCE - Norma Puspita (Jurnal Tekno Global, 2018)
Pagar Alam City has high rainfall with highland topography that to trigger landslide events, especially in villages area and road at hillside. It affects to road networks activity which affected by road failure and inhibit vehicles traffic. This study will analyzed landslide vulnerability in main road of Pagar Alam City based on topography characteristic, geology, and soil types. Distribution of landslide occurrences will assessed base on landslide occurences density in unit areas. Frequency and distribuition of landslide occurrences will analyzed by landslide trigger factors such as stability, slope, soil type and geology, infrastructures type. Meanwhile rainfall extreme events period will be analyzed with general numbers extreme model. Finally, landslide vulnerability will be analyzed with spatial multi criterias evaluation (SMCE) ILWIS due to availability of input map factors, such as poin of landslide, sloppe, soil type, geology, drainage system, infrastructure, and landcover. The result of this study showed that distribution of landslide hazard potential will be occurred in Shouth Dempo District with 12605 hectares for high and very high landslide hazard potentials.Keywods: Landslide, SMCE, ILWIS